\(B=1-\left(\dfrac{1}{2.6}+\dfrac{1}{4.9}+\dfrac{1}{6.12}+...+\dfrac{1}{35.67}+\dfrac{1}{38.60}\right)\left(1\right)\)
Đặt \(S=\dfrac{1}{2.6}+\dfrac{1}{4.9}+\dfrac{1}{6.12}+...+\dfrac{1}{35.67}+\dfrac{1}{38.60}\)
\(S=\dfrac{1}{2.3.\left(1.2\right)}+\dfrac{1}{2.3.\left(2.3\right)}+\dfrac{1}{2.3.\left(3.4\right)}+...+\dfrac{1}{2.3.\left(18.19\right)}+\dfrac{1}{2.3.\left(19.20\right)}\)
\(S=\dfrac{1}{6}.\left(\dfrac{1}{1.2}+\dfrac{1}{2.3}+\dfrac{1}{3.4}+...+\dfrac{1}{18.19}+\dfrac{1}{19.20}\right)\)
\(S=\dfrac{1}{6}.\left(1-\dfrac{1}{2}+\dfrac{1}{2}-\dfrac{1}{3}+\dfrac{1}{3}-\dfrac{1}{4}+...+\dfrac{1}{18}-\dfrac{1}{19}+\dfrac{1}{19}-\dfrac{1}{20}\right)\)
\(S=\dfrac{1}{6}.\left(1-\dfrac{1}{20}\right)=\dfrac{1}{6}.\dfrac{19}{20}=\dfrac{19}{120}\)
\(\left(1\right)\Rightarrow B=1-\dfrac{19}{120}=\dfrac{101}{120}\)
Đạ biểu thức trong dấu ngoặc đơn là A
\(A=\dfrac{1}{2.1.3.2}+\dfrac{1}{2.2.3.3}+\dfrac{1}{2.3.3.4}+\dfrac{1}{2.4.3.5}+...+\dfrac{1}{2.18.3.19}+\dfrac{1}{2.19.3.20}=\)
\(=\dfrac{1}{2.3}\left(\dfrac{1}{1.2}+\dfrac{1}{2.3}+\dfrac{1}{3.4}+\dfrac{1}{4.5}+...+\dfrac{1}{18.19}+\dfrac{1}{19.20}\right)=\)
Đặt biểu thức trong dấu ngoặc đơn là C
\(C=\dfrac{2-1}{1.2}+\dfrac{3-2}{2.3}+\dfrac{4-3}{3.4}+...+\dfrac{20-19}{19.20}=\)
\(=1-\dfrac{1}{2}+\dfrac{1}{2}-\dfrac{1}{3}+\dfrac{1}{3}-\dfrac{1}{4}+...+\dfrac{1}{19}-\dfrac{1}{20}=\)
\(=1-\dfrac{1}{20}=\dfrac{19}{20}\)
\(\Rightarrow B=1-\dfrac{1}{6}.C=1-\dfrac{1}{6}.\dfrac{19}{20}=\dfrac{101}{120}\)